Mengatasi Kemiskinan Melalui Zakat di Malaysia: Kajian Terhadap Tiga Faktor Yang Mempengaruhinya - Muhammad Syukri Salleh (Media Syari'ah, 2017)
Zakat is believed to be addressing the problem of poverty, but why poverty among Muslims is still high? According to The Nation (July, 29, 2014), rather than the 1.7 billion poor people in the world in the year 2011, 44 percent thereof living in Muslim countries. What realities which are not subjected to the control of up to present zakat poverty among Muslims in Muslim countries are still not able to overcome? This paper examines this issue with three realities that has association with charity and poverty. The Three realities are that the nature of zakat, zakat pentadbiran structure, and the poverty measure used. Third-three is believed to reality is a factor that should be restraint in the care of poverty through zakat. Almost all the argument in this paper is based on the experience in Malaysia.